REPUTATION MANAGEMENT OF A BRAND IN THE AGE OF SOCIAL MEDIA AND DIGITAL COMMUNICATIONS - VDOVICHENA, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article reveals the features of effective brand reputation management in the context of digital communications and social networks. It is established that strategic reputation management requires a comprehensive approach, including the use of various content marketing methods tailored to the specifics of each digital platform. It is clarified that an important aspect is the adaptation of content to different communication channels, such as social media, blogs, and review platforms. The importance of creating content that aligns with the interests of the target audience, which enhances the effectiveness of brand communications, is emphasized. The role of content marketing in shaping the company's image as an expert in its field, which helps attract new customers and strengthen brand trust, is underlined. It is stated that to ensure high communication effectiveness, it is essential to consider the features of each platform and adapt publication strategies accordingly. It is determined that social media are the primary channels for building brand reputation due to their ability to provide fast information exchange and audience interaction. It is noted that an important strategy is the integration of social media into the overall communication strategy, allowing the creation of a unified brand reputation line across all platforms. The significance of data analytics for monitoring communication effectiveness and timely adjustment of the brand's strategy is emphasized. The importance of implementing innovative communication methods, such as interactive platforms and the use of user-generated content, to strengthen brand trust is highlighted. It is determined that the success of brands on social media depends on a clear understanding of audience needs and preferences, as well as on the use of various content targeting approaches. It is noted that it is necessary to consider the emotional impact of content and its adaptation to the specifics of each platform for maximum effect.
Keywords: reputation management; brand; digital communications; social networks; content marketing; platforms; brand trust; communication strategies; data analytics; branding; content; targeting